Youth Entrepreneurs Characteristic and Motivation - Kamall Khan, Yasmin; Zannierah Syed Marzuki , Sharifah (International Journal of Psychosocial Rehabilitation, 2020)
Regardless of any country, entrepreneurship contributes to the economic growth of a nation. Nevertheless, the number of people involved in entrepreneurship remains low, instead of a high unemployment rate. This contradiction between youth attitudes and action highlights the need for programs that support the development of entrepreneurship in today’s youth. A suitable program or incubator can be designed for these youth. But before a suitable program can be designed for this target group, we have to understand their personality and motivation. Data for this study was collected using qualitative methods. The qualitative data come from semi-structured interviews. This interview was conducted by inviting five young entrepreneurs that consist of three part time entrepreneurs from the Master in Applied Entrepreneurship in UiTM, and the other two entrepreneurs actively involved with business currently. The results show that youth’s characteristics are influenced by self-efficacy, initiative, and information seeking, while their motivation is driven by passion and family support, which are important for promoting entrepreneurial intent among young adults. Youth has a creative way of thinking and is motivated to run their businesses with an appropriate exposure in the higher learning institution.